pH-Responsive PLGA Nanoparticle for Controlled Payload Delivery of Diclofenac Sodium - Shalil Khanal; Udhab Adhikari; Nava P. Rijal; Shanta R. Bhattarai; Jagannathan Sankar; Narayan Bhattarai (Journal of Functional Biomaterials, 2016)
Poly(lactic-co-glycolic acid) (PLGA) based nanoparticles have gained increasing attention in delivery applications due to their capability for controlled drug release characteristics, biocompatibility, and tunable mechanical, as well as degradation, properties. However, thorough study is always required while evaluating potential toxicity of the particles from dose dumping, inconsistent release and drug-polymer interactions. In this research, we developed PLGA nanoparticles modified by chitosan (CS), a cationic and pH responsive polysaccharide that bears repetitive amine groups in its backbone. We used a model drug, diclofenac sodium (DS), a nonsteroidal anti-inflammatory drug (NSAID), to study the drug loading and release characteristics. PLGA nanoparticles were synthesized by double-emulsion solvent evaporation technique. The nanoparticles were evaluated based on their particle size, surface charge, entrapment efficacy, and effect of pH in drug release profile. About 390–420 nm of average diameters and uniform morphology of the particles were confirmed by scanning electron microscope (SEM) imaging and dynamic light scattering (DLS) measurement. Chitosan coating over PLGA surface was confirmed by FTIR and DLS. Drug entrapment efficacy was up to 52%. Chitosan coated PLGA showed a pH responsive drug release in in vitro. The release was about 45% more at pH 5.5 than at pH 7.4. The results of our study indicated the development of chitosan coating over PLGA nanoparticle for pH dependent controlled release DS drug for therapeutic applications.